Intermolecular Chirality Modulation of Binaphthalene-Bridged Bisporphyrins With Chiral Diamines - Lu, Wenxin; Gong, Lei; Su, Chaorui; Wang, Qibao; Ling, Qing; Wang, Peng; Qi, Dongdong; Bian, Yongzhong (Frontiers in Chemistry, 2021)
A new pair of 2,2ʹ-diamino-1,1ʹ-binaphthyl linked porphyrin dimers, (R)-/(S)-H, were synthesized to study their supramolecular interactions with a pair of chiral diamines ((R)-/(S)-PPDA) by using UV-Vis absorption, fluorescence and NMR titrations. The spectroscopic titrations indicated that sandwich-type 1:1 complexes were formed at low guest concentration and then transformed to 1:2 open complexes at high guest concentration. The supramolecular interactions afforded sensitive circular dichroism responses, and the CD signs of the 1:1 complexes are decided by the stereostructure of chiral diamine guests. Moreover, due to the shortened linking units, (R)-/(S)-H show more sensitive and predicable CD response than the previously reported hosts (R)-/(S)-H1 and this can be reasonably explained by DFT molecular modeling. The present results suggest (R)-/(S)-H are promising for chiral optical sensing.